Effects of Heat Generation and Chemical Reaction on Time-Dependent MHD Natural Convective Transport Past in a Vertical Perforated Sheet (Journal of Engineering Science, 2024)
This investigation focused on the impacts of heat production and chemical reaction on time-dependent MHD-free convective transport via a vertical permeable sheet. The ODEs are obtained by transforming the governing PDEs using similarity transformations. With the assistance of MATLAB software, the shooting technique is utilized to numerically resolve the non-dimensional governing equations with boundary conditions. The role of emerging non-dimensional parameters or numbers like the Schmidt number , heat generation parameter (Q), Prandtl number , and chemical reaction parameter (Kr) on fluid temperature, velocity, and concentration were discussed within the boundary layer. The results show that temperature and fluid motion are improved by raising the heat generating parameters. On the contrary, as the chemical reaction value goes up, the fluid velocity and concentration do as well.Journal of Engineering Science 14(2), 2023, 137-144